Efektifitas Media Evaluasi Berba Efektifitas Media Evaluasi Berbasis Wordwall pada Pembelajaran Pendidikan Pancasila: Efektifitas Media Evaluasi Berbasis Wordwall pada Pembelajaran Pendidikan Pancasila - Putera, Rafhi Febryan; Nababan, Kesnawati; Etri Wahyuni; Yesni Yenti; Afriza Media (Journal of Practice Learning and Educational Development, 2025)
The purpose of this study was to improve the effectiveness of Wordwall media on student learning outcomes in Grade IV of Elementary School in Pancasila Education Learning. The type of research used is research and development (Research and Development) with the ADDIE model consisting of five stages, namely analysis, design, development, implementation, and evaluation. Research instruments with tests, observations and questionnaires. Research data obtained from the pretest and posttest in the form of a percentage of the total score of each respondent and the average. The results of the study showed that there was an increase in learning outcomes with the application of Wordwall media, this was evidenced by the learning outcomes in the posttest, namely the percentage of students who completed the trial school SDN 26 Sungai Nanam obtained a percentage of 94.73%, then at the Implementation school SDN 02 Sungai Nanam obtained a percentage of 82.60% and the Effectiveness Test at SDN 18 Sungai Nanam 88%. Thus it can be concluded that the Wordwall-based evaluation media in grade IV of Elementary School is declared effective for use.